(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research is to examine the effect of visual and scent on perceived intimacy of a service provider and consumers’ dental anxiety, in the context of the healthcare industry, specifically dental clinic service. Further, this study also examined the possibility of interaction effect of visual and scent on both variables. A 2x2, full factorial, an experimental research design was conducted throughout a four-day experiment in a marketing lab of a large private university in Indonesia. The tools needed to analyse the data are SPSS data processing devices. Sampling method used in this study is nonprobability sampling - purposive sampling by making criteria to have visited a dental clinic. This research managed to collect a total of 144 samples. Findings show that visuals only have a significant effect on store intimacy and dental anxiety. Scent has no significant effect on any of the variables we study. Additionally, we found no interaction effect between visual and scent in this context.